2013
DOI: 10.3389/fphys.2013.00294
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability in normal and pathological sleep

Abstract: Sleep is a physiological process involving different biological systems, from molecular to organ level; its integrity is essential for maintaining health and homeostasis in human beings. Although in the past sleep has been considered a state of quiet, experimental and clinical evidences suggest a noteworthy activation of different biological systems during sleep. A key role is played by the autonomic nervous system (ANS), whose modulation regulates cardiovascular functions during sleep onset and different slee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
186
1
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 282 publications
(234 citation statements)
references
References 124 publications
9
186
1
10
Order By: Relevance
“…(20) However, the extant research literature has not been able to replicate these findings with comparable detail and instead yielded somewhat inconsistent, divergent findings. (21) Whilst two reviews examining HRV, sleep and sleep disorders have been published previously they did not systematically synthesise the findings of the insomnia -HRV literature and we were aware of additional studies that were not included (5,13). Therefore, the aim of this review was to identify all HEART RATE VARIABILITY IN INSOMNIA PATIENTS …”
Section: Insert Table 1 About Herementioning
confidence: 99%
See 1 more Smart Citation
“…(20) However, the extant research literature has not been able to replicate these findings with comparable detail and instead yielded somewhat inconsistent, divergent findings. (21) Whilst two reviews examining HRV, sleep and sleep disorders have been published previously they did not systematically synthesise the findings of the insomnia -HRV literature and we were aware of additional studies that were not included (5,13). Therefore, the aim of this review was to identify all HEART RATE VARIABILITY IN INSOMNIA PATIENTS …”
Section: Insert Table 1 About Herementioning
confidence: 99%
“…(5, 9, 13) Accordingly, the research focus has shifted to investigating the associations between HRV, sleep disorders and their subsequent comorbidities and the incorporation of non-traditional HRV techniques. (5,13,14) Given the interplay between HRV and cardiac autonomic activity, the use of HRV in insomnia research may assist further investigation into the pathophysiology and potential health impacts of insomnia. Hyperarousal has been defined as 'a state of increased arousal at the physiological, cortical, cognitive or emotional level' (15) and hypothesised to contribute to the development, maintenance and 24-hour systemic sequelae of insomnia.…”
Section: Insert Table 1 About Herementioning
confidence: 99%
“…Several studies have shown that OSA affects the normal variation of heart rate and that both HRV [5,7,15,31] and PRV [9,32] might help identifying OSA events. Some studies have suggested that certain nonlinear measures of HRV are better predictors of future adverse events in various patient groups than the standard linear measures [13].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, analysis of heart rate variability (HRV) has been investigated as a possible predictor of OSA [5][6][7]. Studies have shown that OSA affects the normal variation of heart rate and that both HRV and pulse rate variability (PRV), a surrogate measure of HRV estimated from the photoplethysmogram (PPG) [8], may assist with the identification of OSA events [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…REM sleep has a parasympathetically medicated tonic component and sympathetically mediated phasic component. The phasic component of REM sleep is characterized by skeletal muscle twitches, increased heart rate variability, pupil dilation, and increased respiratory rate [16][17][18]. During NREM sleep, the metabolic demand of the brain decreases and the blood flow throughout the entire brain progressively decreases [19][20][21].…”
Section: Oxgen Desaturation During Sleep In Copd Patients and Sleep Pmentioning
confidence: 99%